A Computationally Efficient PM Power Loss Derivation in Thermal Modelling for Surface-mounted Brushless AC PM Machine. (May 2017) - Zhang, Chengning; Liu, Haipeng; Wu, Xiaopeng; Yang, Yongxi; Xinxin,
Abstract: This paper presents a further developed PM power loss mapping methodology from previous authors' work, which further accounts for the temperature effect compared with the former method. Here, a first-order polynomial and a second-order polynomial are used to model the temperature behaviour of resistivity of SmCo and NdFeB material separately. The computationally efficient method presented requires four discrete time-step FEA solutions at a single temperature accounting for open-circuit, rated current in the quadrature axis, rated current in the direct axis and reduced current in the direct axis. The loss predictions from the FE analyses are then used to define a functional representation which accounts for the temperature effect of the magnet loss by incorporating a temperature correction. The proposed method has been validated on two surface-mounted brushless AC PM machine designs showing good agreement with direct FE predictions of the PM power loss.